Penegakan dan Pengawasan Hukum Terhadap Tenaga Kerja Asing dalam Jabatan Struktural Perusahaan - Rizkyka Giovani, Sheline; Mandiana, Sari; Widjiastuti, Agustin (UNES Law Review, 2024)
Foreign nationals who enter Indonesia for work must be filtered and their use limited, especially in placement in structural positions in companies, bearing in mind the mandate of the Manpower Law which must prioritize Indonesian citizens in all available positions or positions. This research uses a normative juridical research type, research is carried out through literature study using a statutory approach and a conceptual approach. This research aims to find out the truth regarding the placement of foreign workers in personnel positions in a company along with the legal consequences for foreign workers themselves and companies who abuse their positions based on statutory regulations. The results of the analysis in this research show that the placement of foreign workers in personnel positions is not justified because it violates the provisions of Law Number 13 of 2003 concerning Employment, Government Regulation Number 34 concerning the Use of Foreign Workers, and the Job Creation Law. The legal consequences of violations for companies are in the form of criminal sanctions or administrative sanctions, while for foreign workers there are no statutory regulations that specifically regulate the legal consequences.